Fiscal Competition and Public Debt - Eckhard Janeba; Maximilian Todtenhaupt (Center for Economic Studies and ifo Institute (CESifo), 2016)
The implications of high indebtedness for strategic tax setting in internationally integrated capital markets have found little attention so far. We analyze when and how changes in initial debt levels affect the distribution of economic activity across space. When public borrowing is constrained, a rise in a country's initial debt level lowers investment in public infrastructure and makes tax setting more aggressive in that country, while the opposite occurs elsewhere. On net a country with higher initial debt becomes a less attractive location. Our model is consistent with the observation that highly indebted countries have decreased corporate tax rates over-proportionally. It sheds light on proposals to devolve taxing power to lower levels of governments which differ in initial debt levels.
Keywords: H25; H63; H73; H87; 330; asymmetric tax competition; business tax; sovereign debt; inter-jurisdictional tax competition